Optimization of formulation and parameters for baking pães de queijo in a microwave oven - Bianchini, Giulia Silva; Andrade, Luan Alberto; Pereira, Joelma (Disciplinarum Scientia | Naturais e Tecnológicas, 2025)
This study used a sequential strategy of experimental statistical design to obtain optimal formulation conditions and baking parameters for pão de queijo (Brazilian cheese bread), in a microwave oven. Plackett & Burman was used for screening the design of ingredients of the pão de queijo formulation and baking parameters in a microwave oven. The significant factors with the greatest effects on the response variables were selected for the Central Rotational Composite Design to optimize the process. The response variables analyzed in both designs were expansion, texture, weight loss, and density of pães de queijo. The optimization conditions achieved were 55% milk, 40% cheese, three minutes of baking time, and 80% power of the actual power of the microwave oven. The physical characteristics of pães de queijo formulated and baked with the optimal conditions found in this research are not similar to those baked in conventional ovens found in the literature.